2013
DOI: 10.1002/pon.3257
|View full text |Cite
|
Sign up to set email alerts
|

Young adult daughters of BRCA1/2 positive mothers: What do they know about hereditary cancer and how much do they worry?

Abstract: Targeted professional attention to this high-risk cohort of young women is critical to inform the next generation of daughters of BRCA1/2 mutation carriers and encourage recommended screening by age 25 years. Improved uptake of screening and risk reduction options could improve survival, and psychoeducation could reduce cancer-related distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 33 publications
5
86
0
Order By: Relevance
“…Many participants reported having grown up without awareness or with misinformation about the genetic disease running in their family or its inheritance mode: 12,16,21 they also lacked information about the appropriate age for testing. 12,16 Two sets of authors reported that the first communication about the genetic risk was made by parents. 14,16 None of the participants was younger than 12 years of age when informed, about half experienced disclosure before they were 18 years old and half between 18 and 21 years old.…”
Section: Presymptomatic Genetic Testing In Young Adultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many participants reported having grown up without awareness or with misinformation about the genetic disease running in their family or its inheritance mode: 12,16,21 they also lacked information about the appropriate age for testing. 12,16 Two sets of authors reported that the first communication about the genetic risk was made by parents. 14,16 None of the participants was younger than 12 years of age when informed, about half experienced disclosure before they were 18 years old and half between 18 and 21 years old.…”
Section: Presymptomatic Genetic Testing In Young Adultsmentioning
confidence: 99%
“…12,16 Two sets of authors reported that the first communication about the genetic risk was made by parents. 14,16 None of the participants was younger than 12 years of age when informed, about half experienced disclosure before they were 18 years old and half between 18 and 21 years old. Many participants stated that the disclosure was made during an occasional encounter and in a casual moment (ie, while driving) or by telephone.…”
Section: Presymptomatic Genetic Testing In Young Adultsmentioning
confidence: 99%
See 3 more Smart Citations